ACIDIC SOAKING AND STEAM BLANCHING RETAIN ANTHOCYANINS AND POLYPHENOLS IN PURPLE Dioscorea alata FLOUR [Perendaman Asam dan Blanching Uap Mempertahankan Antosianin dan Polifenol Tepung Dioscorea alata Ungu] - Nelis Imanningsih; Deddy Muchtadi; Tutik Wresdiyati; Nurheni Sri Palupi; . Komari (Jurnal Teknologi dan Industri Pangan, 2013)
Purple Dioscorea alata (DA) tuber has health benefits due to its bioactive anthocyanins, which belong to polyphenolic group. Tuber is commonly made into flour to optimize its uses, however, the anthocyanins undergo significant degradation during processing because of the endogenous polyphenol oxidase activities. This research investigated factors that retain anthocyanins and polyphenols in the purple DA flour as well as its antioxidant capacity. The types of treatments during milling process should be taken into account; for instance, soaking in citric acid and blanching in order to preserve the bioactive compounds. To examine the inhibitory effects of acidic soaking and steam blanching on polyphenol oxidase activities, these experiments used four levels of citric acid (0, 0.25, 0.5, and 1%) and two levels of steam blanching time course (5 and 10 minutes). It was found that steam blanching for 5 or 10 minutes could reduce the activity of polyphenol oxidase, and consequently, retard the oxidation process and retain the polyphenolic compounds. Soaking the purple DA slices into a 1% citric acid solution followed by steam blanching for 10 min resulted in the highest total anthocyanins (104.36 mg/100 g), polyphenols (198.52 mg equivalent gallic acid/100 g), with an antioxidant capacity of 1.300 mg trolox equivalent/100 g. This study showed that the retention of bioactive compounds of DA tuber through soaking the tuber slices in solution containing inexpensive chemicals like citric acid at low concentrations, combined with 10 minutes of steam blanching resulted in flour containing total anthocyanins and phenolic as high as 44.51% and 62.58% of fresh tuber, respectively.